Correlation Between Uric Acid/High Density Lipoprotein Cholesterol Ratio and Postoperative AKI in Patients with CABG - Jiang F; Peng Y; Hong Y; Cai M; Li S; Xie Y; Chen L; Lin Y (International Journal of General Medicine)
Fei Jiang,1– 3,* Yanchun Peng,1,2,* Yuezhen Hong,4,* Meiling Cai,1– 3 Sailan Li,1 Yuling Xie,1,3 Liangwan Chen,1,3 Yanjuan Lin1– 3 1Department of Cardiovascular Surgery, Fujian Medical University Union Hospital, Fuzhou, People’s Republic of China; 2Department of Nursing, Fujian Medical University Union Hospital, Fuzhou, People’s Republic of China; 3Key Laboratory of Cardio-Thoracic Surgery (Fujian Medical University), Fujian Province University, Fuzhou, People’s Republic of China; 4Fujian Medical University, Fuzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Liangwan Chen; Yanjuan Lin, Email fjxhlwc@163.com; fjxhyjl@163.comObjective: This study aims to investigate the association between preoperative serum uric acid to high-density lipoprotein cholesterol ratio (UHR) and the occurrence of postoperative acute kidney injury (AKI) in patients who underwent coronary artery bypass grafting (CABG).Methods: A prospective observational study was conducted at Fujian Heart Medical Center between May 2022 and December 2023, recruiting patients scheduled for CABG. Participants were categorized into two groups based on AKI occurrence post-surgery. Univariate and multivariate logistic regression analyses were performed to identify predictor variables for AKI after CABG. A nomogram was constructed based on these predictors, and its calibration was evaluated using the receiver operating characteristic curve (ROC) and Hosmer-Lemeshow goodness of fit test. The diagnostic value of UHR in AKI after CABG was explored using the area under the curve (AUC).Results: The study included 301 CABG patients, of whom 72 (23.92%) developed AKI. After adjusting for age, gender, body mass index, and extracorporeal circulation, binary logistic regression analysis revealed that a higher UHR value was an independent risk factor for developing AKI after CABG (OR=7.410, 95% CI: 3.829– 14.855), P < 0.05. The prediction nomogram demonstrated excellent discriminability, with an AUC of 0.87 and good calibration (Hosmer-Lemeshow test, P < 0.05). Compared with other clinical indicators, ROC analysis indicated that UHR had the largest AUC (0.821), corresponding to 70.8% sensitivity and 79.0% specificity.Conclusion: Higher UHR was associated with an increased risk of AKI after CABG and may serve as a prospective biomarker for predicting AKI.Keywords: UHR, CABG, AKI, Nomogram